Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1103/physrevb.82.075322
|View full text |Cite
|
Sign up to set email alerts
|

Proton migration mechanism for operational instabilities in organic field-effect transistors

Abstract: . (2010). Proton migration mechanism for operational instabilities in organic field-effect transistors. Physical Review B, 82(7), 075322-1/11. [075322]. DOI: 10.1103/PhysRevB.82.075322 DOI:10.1103/PhysRevB.82.075322 Document status and date:Published: 01/01/2010 Document Version:Publisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) Please check the document version of this publication:• A submitted manuscript is the version of the article upon submission and before pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 31 publications
3
51
0
Order By: Relevance
“…It has been reported that the time scale for recovery then depends on the extent of stressing [22]. Here we have investigated the recovery of the ZnO transistors as a function of the trapped charge density.…”
Section: Threshold Voltage Dynamicsmentioning
confidence: 99%
“…It has been reported that the time scale for recovery then depends on the extent of stressing [22]. Here we have investigated the recovery of the ZnO transistors as a function of the trapped charge density.…”
Section: Threshold Voltage Dynamicsmentioning
confidence: 99%
“…[11][12][13][14] Proximal probe techniques, such as scanning Kelvin probe microscopy (SKPM), allow us to fully explore the structure-property relationships in working OTFT structures. [14][15][16][17][18][19][20][21][22][23][24][25] SKPM provides the ability to monitor changes in charge transport phenomena in both space and time, a capability not afforded by traditional electrical performance measurements a Author to whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…The fast saturation of the threshold voltage shift and the recovery time in EGOFETs is attributed to the large diffusion constant of protons in PSS as compared to SiO 2 (D $ 10 À19 m 2 s À1 ). 12,34 The migration of protons leads to the accumulation of protons in the gate insulator, which partially screens the applied gate voltage by creating an electric field that is compensated for by the gate voltage in order for an accumulation layer to be formed, and thus the threshold voltage of the OFET increases. Longer periods of time of the gate voltage application leads to larger number of holes converted into protons, and hence a larger increase or shift in the threshold voltage.…”
Section: -3mentioning
confidence: 99%
“…8,12,21,29 The mechanism proposed by several authors implies an electron transfer from adsorbed water present at the semiconductor/SiO 2 interface to positively charged semiconducting channel in the transistor (P3HT þ ). The products of the water oxidation are a proton and a dioxygen…”
mentioning
confidence: 99%
See 1 more Smart Citation